Prevalence of overweight and obesity and their impact on academic performance and psychological well-being among university students in 2024 in Bangladesh. - Hasibul Hassain Emon; Soham Sarker; Mst Shamima Akter Lima; Farzana Afroze Tasnim; Abdullah Al Nabil; Muhammad Ibrahim Azam; Md Moyazzem Hossain (PLoS ONE)
Background The prevalence and impact of obesity and overweight is one of the main concerns among researchers worldwide. There are several consequences of overweight and obesity among students in developing countries like Bangladesh. Therefore, this study aims to explore the prevalence and impact of overweight or obesity on individuals' self-esteem and academic performance among university students in Bangladesh. Methods and materials This study is based on primary data that was collected from 600 students of Jahangirnagar University using a well-structured questionnaire. The questionnaire included demographic information, the Rosenberg Self-Esteem Scale (RSES), and the International Physical Activity Questionnaire (IPAQ-7). The summary statistics, the Fisher exact test, the Chi-square test, and the Pearson correlation matrix were computed. A logistic regression model assessed the relationship between low self-esteem and other variables such as demographic characteristics, BMI status, and physical activities. Results The findings indicate that 38.2% of the students are overweight or obese, and the prevalence rate is high among males. The lowest academic performance across all disciplines is observed among obese students. A negative correlation is observed between BMI and self-esteem (r = -0.41) and academic performance is negatively linked with overweight or obese (r = -0.26) Results depict that overweight/obese students are 7.11 times more likely to have low self-esteem (AOR: 7.11, 95% CI: 4.59-11.02) compared to normal students. Conclusions Overweight and obese students are more prone to lower academic performance and low self-esteem, considering physical inactivity and irregular dietary patterns. Therefore, university authorities ought to encourage students to engage in physical activities and should create awareness among students about the beneficial effects of nutritious foods and the importance of physical exercise.